Optimization Of Bacterial Cellulose Production From Acetobacter Xylinum By Using Response Surface Methodology (Rsm) - Jaleha, Sathar (2012)
Nowadays, the application of cellulose as renewable polymer and bio materials has been a great attraction for most researchers to optimize the production of cellulose through the fermentation of Acetobacter Xylinum sp. The latest technology of the optimization process which known as Response Surface Methodology (RSM) was applied to determine the significant variables that affect the fermentation of bacterial cellulose. The variables were selected as temperature, pH and glucose concentration of the medium. Prior RSM, OFAT was conducted to determine the minimum range for each variable. The minimum range of temperature was selected at 25, 27, 29, 31 and 33 °C. pH was at 4,5,6,7 and 8, meanwhile glucose concentration was at 0, 2, 4, 6, 8 and 10 g/L. The range of optimum value for each variable determined from OFAT was inserted into RSM for further optimization. From the statistical analysis of RSM, all the three variables proved to significantly affect the fermentation process by probability value less than 0.05. Further optimization of the fermentation by using temperature at 29.2 °C, pH at 5.83 and glucose concentration at 1.75 g/L was enhanced the yield of bacterial cellulose at 3.6 times than the conventional fermentation condition, where 17.81 g of bacterial cellulose was determined after the optimization process. The typical spectrum of cellulose which consists of C-O ether bond, hydroxyl bond and C-H bond was successfully determined from the bacterial cellulose sample at wave number of 3331, 2920, 1500–1300 and 1025 cm-1 respectively from FTIR analysis. Meanwhile, the observation by SEM on the treated and untreated bacterial cellulose showed different observation of fibre network, where the treated bacterial cellulose showed clear fibre network as compared to the untreated sample. As the conclusion, the objective of the study was accomplished as the yields of bacterial cellulose were optimized 3.6 higher as compared to conventional method and the variables of pH, temperature and glucose concentration was proved significantly affected the bacterial cellulose fermentation process. Further investigation on other variables that affecting the fermentation process such as nitrogen sources concentration and cultivation technique by using other Box Behken and Plucket Burman as the optimization tools are suggested in order to analyze the benefits of the optimization tools provided by Design of Experiment (DOE).